Assessment of reactive oxygen species status and neuroprotection by vitamin e in chronic cerebral ypoperfusion-induced neurodegeneration in rats - Sayeed, Sayyada; Saxena, Anil Kumar; Talib, Norlelawati A.; Azzubaidi, Marwan Saad (2015)
A persistent reduction in regional cerebral blood flow (CBF) compromises memory and cognitive functions in the elderly leading to neurological illnesses. To unravel the neuropathological consequences of a reduced CBF a similar condition has been created in rats by common carotid artery occlusion (2 vessel occlusion, 2VO). Since oxidative stress, leading to neuronal death, is a major risk factor in neurodegenerative disorders, the present study was designed to assess the neuroprotective role of Vitamin E (Vit E) in chronic cerebral hypoperfusion induced-neurodegeneration. After acclimatization, twenty four Sprague Dawley rats weighing 200-250 g were equally divided into three groups. Group A – sham control, Group B–2VO, and Group C–2VO-E (treated daily with Vit E, 100 mg/kg, orally following 2VO). On the 8th week, all the rats were euthanized and the hippocampi were isolated. Viable neuronal cell count in the hippocampal CA-1 region was estimated. The Isoprostane F2 (Iso-F2) levels were also measured in the brain homogenates to quantify the oxidative stress levels. There was significant difference in neuronal cell death in 2VO group as compared to sham group. In 2VO-E rats, the viable neuronal cell count of the hippocampal CA-1 region was significantly higher (p<0.05) as compared to the 2VO group. Moreover, Iso-F2 levels in 2VO group was significantly higher (p<0.05) as compared to 2VO-E group, implying high oxidative stress in 2VO group and reduction of oxidative stress levels in 2VO-E group. This study clearly demonstrates the effectiveness of Vit E as a neuroprotective and antioxidant agent in chronic cerebral hypoperfusion induced-neurodegeneration in rats.